الدور التمويلي للمصارف العراقية في تحقيق النمو الاقتصادي - حسن كریم حمزة (مجلة الغري للعلوم الاقتصادية والادارية)
الملخص أصبح وجود قطاع مصرفي متطور من المقومات الاساسیة لتحقیق نمو مستدام، فلا قطاع خاص متطور بدون مساندة ودعم من القطاع المصرفي، القطاع المصرفي الع ا رقي یعیش الیوم مرحلة الاصلاح المصرفي لجعله اكثر كفاءة وفاعلیة، لقد تم د ا رسة المؤش ا رت المالیة لهذا القطاع للوقوف علیها ومقارنتها مع المؤش ا رت المشابهة لها على الصعید العربي والدولي وتبین انها مع جوانب الاصلاح في بعضها، في حین لا ا زلت الاخرى بعیدة عن المؤش ا رت الدولیة القیاسیة، تم ایجاد العلاقة بین الائتمان المقدم للقطاع الخاص والنمو في الع ا رق واتضح العلاقة الایجابیة بین المتغیرین، كما توصل البحث إلى بعض الاستنتاجات والتوصیات الضروریة. Abstract Became a banking sector sophisticated essential ingredient to achieve sustainable growth, not the private sector developed without the support and support from the banking sector, the Iraqi banking sector today lives stage banking reform to make it more efficient and effective, we have been studying the financial indicators for this sector to stand by and compared with indicators similar her at the Arab and international shows it with aspects of reform in some of them, while still other far from international indicators standard, found the relationship between the credit extended to the private sector and growth in Iraq and turned positive relationship between the two variables, as research has reached some conclusions and recommendations necessary.